The evolutionary mechanisms for tolerance and social humanism development in education and medicine: a post-capitalist discourse - Utiuzh, I. H.; Kovtun, N.; Hrebin, S.; Vlasenko, F.; Volkova, V.; Утюж, Ірина Геннадіївна (My University, 2023)
The article is concerned with the substantive nature of late capitalism, which determines all spheres of social existence. It is clarified that neoliberal ideology forms a special type of socio-cultural relations, in which the politics‟ technocratic nature disregards humanitarian and cultural aspects and doubts the very existence of the social. Under the circumstances of IT intensified development and real crisis of capitalism, the fundamental process of human-human interaction is ignored, consequently resulting in the loss of the human‟s fundamental feature, that is, his sociality. Socio-philosophical research in modern realities is assigned to actualize the issues of spiritual production related to preservation of the social as the ontological essence of society existence in the future. Therefore, our paper aims to analyze the socio-productive function of education and medicine in the formation of a humanitarian and anthropological model of preserving social partnership and tolerance in modern society as opposed to the disappointing and disturbing experience of chronic social pathologies, medicalization and formation of the “remission society” model within the framework of capitalism. The formation of a humanitarian and anthropological model of preserving the social consists in actualizing the evolutionary mechanisms for social humanism, which is the basic characteristic of the post-capitalist reality.
Keywords: post-capitalism; humanitarian and anthropological model; education; medicine; sociality; social partnership; tolerance; academic migration